1985
DOI: 10.1002/ccd.1810110408
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous balloon catheter angioplasty of coarctation of the abdominal aorta: Report of two cases

Abstract: Two patients with coarctation of the abdominal aorta are reported. They both underwent successful transluminal balloon angioplasty. The immediate and short-term results have been excellent. This method and its role in the treatment of coarctation of the abdominal aorta are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

1987
1987
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 11 publications
(3 reference statements)
0
6
0
Order By: Relevance
“…Six patients also had stenoses of 8 renal arteries, and 3 had splanchnic arterial obstructions. '5 bReferences 2,[6][7][8]11,12,13,15,16,[19][20][21][31][32][33][34] 'References 2,5,11,[13][14][15][16]19,[22][23][24][25][26]35,36 dReferences [6][7][8]11,13,15,19…”
Section: Congenitalmentioning
confidence: 99%
See 2 more Smart Citations
“…Six patients also had stenoses of 8 renal arteries, and 3 had splanchnic arterial obstructions. '5 bReferences 2,[6][7][8]11,12,13,15,16,[19][20][21][31][32][33][34] 'References 2,5,11,[13][14][15][16]19,[22][23][24][25][26]35,36 dReferences [6][7][8]11,13,15,19…”
Section: Congenitalmentioning
confidence: 99%
“…The use of stent technology has generated increasing interest in the management of aortic coarctation. [22][23][24][25]27,68,70 Extensive data exist in patients treated for isthmic coarctation27,64,68; however, limited data are available on the efficacy and durability of stent grafting for the MAS. The complex anatomic configuration and variable stenoses of the mesenteric and renal arteries in relation to the abdominal aortic segment afflicted by the MAS1-35 7,8 Ii 13 1 16 19,48 renders endovascular therapy a challenging endeavor.…”
Section: Endovascular Therapymentioning
confidence: 99%
See 1 more Smart Citation
“…Endovascular therapy has been used for MAS with some short-term success. Schechter et al 17 reported on 2 patients who underwent balloon angioplasty with good immediate-and short-term results. Delayed aneurysm formation is reported to occur in 5% to 20% of cases after angioplasty.…”
Section: Discussionmentioning
confidence: 97%
“…A detailed account of balloon angioplasty and stenting in patients with aortic coarctation of the abdominal aorta (middle aortic syndrome) has been previously reported. 17 Schechter and colleagues, 86 Singer and colleagues, 87 Adwani and colleagues, 88 and Fava 89 performed balloon angioplasty for coarctation of the abdominal aorta with or without aorto-arteritis with promising initial success; yet, the long-term outcome was substantially impaired because of a substantial grade of vessel recoil or aneurysm formation caused by multiple tears and cracks in the intima or splits of various grades in the media. 90 Stent technology and its advancement has rekindled interest in the treatment of aortic coarctation; however, only limited data are available on the effect their deployment may have in patients with middle aortic syndrome, particularly in patients with NF-1.…”
Section: Aortic Coarctation/aneurysmal Diseasementioning
confidence: 99%